STUDY ON FACTORS INFLUENCING LABOUR PRODUCTIVITY IN RESIDENTIAL BUILDINGS IN INDIAN SCENARIO - PonmalarV; V, Aravindraj; K, Nandhini (International Journal of Engineering Technologies and Management Research, 2018)
The construction sector is diverse as it contains contractors, consultants, designers, owners and others. Poor productivity of construction workers is one of the causes of cost and time overruns in construction projects. As construction is a labour-intensive industry, this paper focuses on labour productivity in the construction industry and to identify factors affecting labour productivity at building construction project. The performance of labour is affected by many factors and is usually linked to the performance of time, cost, work pressure, safety measures and quality. The questionnaires were distributed to supervisors, project Engineer, labourers, the top 35 factors were identified, categorized into 3 different groups, using SPSS tool, which is analytical software, the factors were analyzed and ranked considering relative importance index were calculated. And also calculated actual productivity for Brick Masonry is taken from sites. The result shows the factors considered which most affects the labour productivity loss in residential buildings and actual productivity versus expected productivity the brick masonry work were calculated.